Supervision of students in a Portuguese veterinary medicine school—students’ and supervisors’ expectations, perceptions, and supervision impact - Cota, João; Cunha, Eva; Bexiga, Ricardo; Oliveira, Manuela (Frontiers in Veterinary Science, 2024)
IntroductionThe student-supervisor relationship can be a major cause of psychological distress experienced by students during their study programs. Misalignment between students’ and supervisors’ expectations and perceptions can originate conflicts, highly affecting the wellbeing of students and hindering the progress of their studies. This study was based on a questionnaire focusing on the perceptions of students and supervisors regarding the most important student attributes and outcomes, supervision expectations and perceptions, and supervision impact on mental health of students from a Portuguese Veterinary Medicine School.MethodsThe participants included 36 students from different study programs (bachelor’s, master’s, doctoral and veterinary specialization) and their corresponding supervisors (three).ResultsThe results indicate that veterinary post-graduate and specialization students and their supervisors share similar expectations regarding key student traits and supervision outcomes. Students expected supervisors to be actively involved, particularly in developing technical skills, and generally rated the supervision as of high or very high quality, emphasizing the importance of supervisors’ commitment. In contrast, supervisors were more focused on fostering students’ autonomy, and their assessments of the supervision quality were more diverse. The factors that most affected student’s mental health were the progress of the research or training program and students’ personal expectations, while supervisors perceived that their expectations also induced a negative impact on students’ mental health.DiscussionFurther and continuous research is needed to better understand both the needs and expectations of students and supervisors in different academic realities, including in Veterinary Medicine schools, from which the information available on the subject is scarce.